Memotret Bentuk-bentuk Toleransi di Desa Kampung Kusamba, Karangasem, Bali - Naniek Kohdrata; Cokorda Gede Alit Semarajaya (http://arl.faperta.ipb.ac.id/, 2021)
Kampung Kusamba Village is a relatively small size village in the Bali Island with a majority Muslim population. The village area is surrounded by villages that are predominantly Hindu. The Kampung Kusamba is an example that tolerance in social life is actualized. This research emphasizes on documenting tolerance between Kampung Kusamba dwellers with the Balinese through architectural forms and folklores, myths, or any other oral histories. The research method used is qualitative. Data were collected using a purposive approach, utilizing an in-depth interview technique to resource persons and photographic surveyed for architectural forms. The analysis was carried out descriptively using an ethnographic domain analysis technique approach. Preliminary findings from this study were that physical architectural features that reflect the local culture are the same or almost the same as Balinese architecture. A form of tolerance was also found in the form of artifacts that reflected the diversity of the population of Kampung Kusamba in the past. Oral histories of the past as a manifestation of the intangible landscape also showed the attitude and tolerance of the people of Kampung Kusamba and the people who live in Bali respectively. Moreover, there was also a story that shows the position and special relationship of Kampung Kusamba with Klungkung Royal.